To invade or not to invade? Exploring the niche-based processes underlying the failure of a biological invasion using the invasive Chinese mitten crab - Zhang, Zhixin (2020)
Invasive alien species represent a serious threat to global biodiversity, causing considerable damage to native ecosystems. To better assess invasion risks, it is essential to better understand the biological processes that determine the success or failure of invasions. The catadromous Chinese mitten crab Eriocheir sinensis, whose native distribution is the Pacific Coast of China and Korea, has successfully invaded and established populations in North America and Europe. In Japan, where E. sinensis is also regarded as potentially invasive and multiple introduction vectors exist, the species is not yet established. These settings can be used to explore niche-based processes underlying the apparent failure of a biological invasion. We first quantified native and invasive realized niches of E. sinensis in freshwater habitats using geometrical n-dimensional hypervolumes. Based on the assumption of niche conservatism, we then projected habitat suitability of this species in Japan using species distribution models (SDMs) calibrated with distinct sets of distribution data: native occurrences, invasive occurrences, and both. Results showed that E. sinensis has undergone either niche shifts or niche contractions during invasions in different areas of the world. Projections from SDMs indicate that although part of Japan is suitable for E. sinensis, this does not include the freshwater habitats around the Ariake Sea, which is considered to be a suitable marine environment for E. sinensis larvae. The mismatch between suitable freshwater and marine environments provides a possible explanation for the failure of establishment of E. sinensis in Japan to date. Our findings have useful general implications for the interpretation of biological invasions.